Income diversification for future stable economy in Saudi Arabia: an overview of the tourism industry - Abdul Aziz, Yuhanis; Md Sidin, Samsinar; Raja Yusof, Raja Nerina (IJECM, 2016)
Since the fall of global oil price in 2014, OPEC leader countries start reducing their dependence on oil income. Saudi Arabia, as the world's largest oil exporter, recognize the need to diversify its income away from oil revenue. Tourism industry in the country is identified as a priority area for government income. Thus, the new leaders in Saudi authorities have begun a project in developing this industry targeting domestic and international visitors. This project required new marketing implementations and modern promotion strategies. Therefore, this conceptual paper will highlight the expected future of tourism industry in Saudi Arabia and the opportunities for developers, operators and investors. In addition, the paper will provide implications for future research in different sectors; marketing strategies, services quality and tourist satisfaction. It will discuss the tourism industry development part of Saudi Arabia 2030 vision that announced on April 2016 and the significance of this market for the government. The paper will shed light on religious tourism destinations in the country as a part of tourism industry and common destination for international visitors. Finally, it will raise the expected issues that might challenge the government and business travel operators in developing this industry.